The Great Gatsby the 1926 Broadway script by Owen Davis ; based upon the novel by F. Scott Fitzgerald - Davis, Owen 1874-1956 (Cambridge University Press, 2024)
The cultural ubiquity of The Great Gatsby is such that it is tempting to think we know almost all there is to say about it. But F. Scott Fitzgerald's most famous work still has the capacity to surprise us. Perhaps few admirers of the novel know that it was also adapted for the stage by Owen Davis. In 1926 a successful production ran at the Ambassador Theater in New York City. This edition presents, for the first time in print, the original Broadway script: a fascinating social and literary document, now all but forgotten. The play re-forged Fitzgerald's novel into a fast-moving dramatization of parties and bootlegging, dancing and drinking, hot jazz, adultery and violence. It afforded an evening of first-rate entertainment for Manhattan theatergoers. Incorporating photographs of the original sets and actors, reviews, and publicity pasted into Fitzgerald's scrapbooks, this volume lifts the curtain anew on a singular drama
Title from publisher's bibliographic system (viewed on 26 Apr 2024)
Keywords: Fitzgerald, F. Scott -- 1896-1940 -- The great Gatsby